ACUTE BRONCHIOLITIS IN CHILDREN: MODERN APPROACHES TO DIAGNOSIS AND CLINICAL ASSESSMENT - Maksudjon Pulotjonov; Furkat Shamsiev; Rano Musajanova; Mukhammadali Karimov (Modern American Journals, 2025)
Bronchiolitis is frequently indicative of a lower respiratory tract infection in infants younger than nine months of age. Some clinical and diagnostic issues, such as bronchiolitis caused by the respiratory syncytial virus, are still unsolved. Unfortunately, 80% of cases of bronchiolitis are thought to be pneumonia, according to the research. Due to comparable X-ray abnormalities between pneumonia and bronchiolitis in young children, antibiotic therapy is often prescribed unnecessarily, and pneumonia is overdiagnoses.